Science at the frontier : volume 1 - Greenwood, Addison (Washington, DC : National Academy Press, 1992)
Report on current research in biology, astronomy, mathematics and other fields of science.
Choice.
Wilson's Public Library.
Young Adult
Keywords: Research; Science; Science -- Research